1996
DOI: 10.1016/0305-0483(96)00025-4
|View full text |Cite
|
Sign up to set email alerts
|

An optimization model for planning natural gas purchases, transportation, storage and deliverability

Abstract: Natural gas local distribution companies (LDCs) face the problem of managing natural gas purchases under conditions of uncertain demand and frequent price change. In this paper, we present a stochastic optimization model to solve this problem. Unlike other models, this model explicitly considers deliverability, the rate at which gas can be added to and withdrawn from a storage facility, as a variable, and considers its role in ensuring a secure supply of gas. Deliverability is often overlooked in gas supply pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 10 publications
0
23
0
1
Order By: Relevance
“…The development of this approach is based on our own work in modeling real world problems (e.g., Bopp, et al, 1996) as well as our teaching experience. A summary of the steps in the form of a class handout that can be used by the instructor is provided as an appendix to the paper.…”
Section: The Translation Approach: An Overviewmentioning
confidence: 99%
“…The development of this approach is based on our own work in modeling real world problems (e.g., Bopp, et al, 1996) as well as our teaching experience. A summary of the steps in the form of a class handout that can be used by the instructor is provided as an appendix to the paper.…”
Section: The Translation Approach: An Overviewmentioning
confidence: 99%
“…If weather follows a predictable pattern, there would still be price movements related to the cost of storage. Gas storage is expensive and can add $.25 to $.40 to a price that is often in the range of $2.00 per thousand cubic feet [Bopp, 1996]. Moreover, gas storage is billed both on the amount stored and on the injection or withdrawal rate of changing the storage level.…”
Section: Market Discussion and Model Developmentmentioning
confidence: 99%
“…This approach provides a convenient way to conduct sensitivity analyses over parameters other than demands. Unlike most prevailing models where deliverability, the maximum amount of gas that can be withdrawn from or injected into storage each day, is given as exogenous, another linear stochastic program proposed by Bopp et al [44] explicitly considers it as a decision variable that closely ties and impacts other variables. A case study of the LDC at Huntsville, Alabama, showed that in order to achieve minimum cost, deliverability must be carefully chosen according to the minimum level of firm transportation requirements and the availability of spot purchases.…”
Section: Contracts For Gas Purchase Transportation and Storagementioning
confidence: 99%